The Kāludāyi-Theragāthā as transmitted in the Pali commentaries. (7th May 2019) - Gamage, Aruna
Abstract: While the Theragāthā contains only ten verses attributed to the Elder Kāludāyi, the Pali commentaries ascribe a further two sets of verses to him. The present article aims to carry out a detailed survey of these verses, which have so far received no scholarly attention, as a contribution to the understanding of the formation of Kāludāyi's verses in the canon and their paracanonical legacy. In this paper, the additional verses of Kāludāyi that appear in the commentaries are critically analysed in light of all other utterances attributed to him, in the canon as well as in the commentaries. The style, syntax, and wordings of specific stanzas of both series will be taken into consideration so as to evaluate their antiquity and their literary quality. When dealing with the rhetorical devices adapted in the stanzas, some Sanskrit poems are also taken into account.